Techniques for Analysing and Reconciling the Progressive Mineral Taxation Regime of Papua New Guinea - Ail, Kaepae Ken (Curtin University, 2018)
The study investigated how progressive tax instruments behave to raise revenues from the mining industry without distorting the investment decision-making. The study used real option and Monte Carlo simulation cash flow tax models and historical data to investigate the revenue collecting potentials of Papua New Guinea’s (PNG) progressive mineral taxation regime. The results show that PNG and mineral endowed nations can successfully capture high magnitude of revenues from the resources sector by making tax instruments more progressive.